Implementation of Genetic Algorithms in The Application of Car Racing Games - Ade Pujianto (Indonesian Journal of Artificial Intelligence and Data Mining, 2021)
The car racing game is a game that has always been popular from the past until now. where this game has lots of interesting gameplay, especially when adding artificial intelligence (AI) which makes the gameplay of the game even more challenging because the game is more dynamic with various levels of difficulty. However, most research on the application of artificial intelligence (AI) to the gameplay of car racing games is only limited to the application of game opponents. using genetic algorithms for innovations in game gameplay. Optimization of the game configuration will also be carried out to determine the level or difficulty level of the game's gameplay. The research flow to be implemented is the indie development method where the development method is used by indie game makers. The output of this research is to make scientific publications in accredited national journals and patent rights for car racing game game products. The contribution to this research is to make gameplay that is different from previous research, namely in making gameplay or applying artificial intelligence (AI) to making arena or racing circuits and optimizing genetic algorithms by adding configuration settings to the genetic algorithm